Heat Transfer Behaviour and Flow Field Characterisation of Impinging Synthetic Jets for a Wide Range of Parameters - Murray, Darina; Persoons, Tim (ASME, 2010)
Impinging synthetic jets are considered as a potential solution for convective cooling, in applications that match their main characteristics (high local heat transfer rates, zero net mass flux, scalability, active control). Nevertheless the understanding of heat transfer to synthetic jets falls short of that available for steady jets. To address this, this paper uses detailed flow field measurements to help identify the main heat transfer mechanisms in impinging synthetic jets. Local heat transfer measurements have been performed for an impinging round synthetic jet at a range of Reynolds numbers between 1000 and 3000, nozzle to plate spacings between 4D and 16D and stroke lengths (L0) between 2D and 32D. The heat transfer results show evidence of distinct regimes in terms of L0/D and L0/H ratios. Based on appropriate scaling, four heat transfer regimes are identified which justifies a detailed study of the flow field characteristics. High speed particle image velocimetry (PIV) has been employed to measure the time-resolved velocity flow fields of the synthetic jet to identify the flow structures at selected L0/H values corresponding to the identified heat transfer regimes. The flow measurements support the same regimes as identified from the heat transfer measurements and provide physical insight for the heat transfer behaviour.
International Heat Transfer Conference IHTC14
PUBLISHED
Washington DC, USA
Keywords: Mechanical Engineering; synthetic jets PIV; heat transfer; Smart & Sustainable Planet